2002
DOI: 10.1300/j006v22n02_04
|View full text |Cite
|
Sign up to set email alerts
|

A Life Needs Model of Pediatric Service Delivery

Abstract: This article presents a life needs model of pediatric service delivery that is based on the values of the intrinsic worth, dignity, and strengths of individuals. This developmental, socio-ecological model outlines the major types of service delivery needs of children and youth with disabilities, their families, and their communities within three spheres of life (the personal, interpersonal, and external spheres). The model legitimizes the concept of need, emphasizes the values of family-centered services, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…While tailoring programs to the community context was common in the identified models and frameworks, the uptake of the program and considerations of whom the program is recruiting were not commonly included. Defining the target population (i.e., recruitment) was specified in the Social Marketing Model [ 76 ], while the equity and accessibility of community-based physical activity programs were included in the Life Needs Model [ 75 ] and STEPs-PA framework [ 49 , 77 ]. Only one model, the Typology of Cultural Adaptation and Programme Theory of Adapted Health Promotion Interventions, incorporated both a defined target population and an assessment of the program’s accessibility [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While tailoring programs to the community context was common in the identified models and frameworks, the uptake of the program and considerations of whom the program is recruiting were not commonly included. Defining the target population (i.e., recruitment) was specified in the Social Marketing Model [ 76 ], while the equity and accessibility of community-based physical activity programs were included in the Life Needs Model [ 75 ] and STEPs-PA framework [ 49 , 77 ]. Only one model, the Typology of Cultural Adaptation and Programme Theory of Adapted Health Promotion Interventions, incorporated both a defined target population and an assessment of the program’s accessibility [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…The topic of building capacity and partnerships in the community was also common among process models. This topic consisted of the components focused on the formalized processes and procedures for partnership (partner organization; n = 4) [ 68 70 , 72 ], the types of organizations that are a good fit for the program and the organizations’ reasons for participating in the program (partners and motives; n = 3) [ 70 , 71 , 75 ], the administration of the program (partnership management; n = 3) [ 70 , 72 , 80 ], and the integration of community members and researchers into the development of the program (community partnership; n = 2) [ 69 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…A comprehensive service delivery model incorporating different approaches (e.g., biomedical model, biopsychosocial, and rehabilitation) is suggested for better outcomes [9]. In pediatric rehabilitation, considering the varied needs of children and adolescents (e.g., physical, mental, emotional, communicative, and relational) in the variety of contexts in which they much function every day (e.g., familial, social, and environmental) and the plethora of stakeholders (e.g., families, school personnel), a holistic model is essential [24]. The comprehensiveness of identified core attributes encompassing core principles of various models (e.g., learner-centred approach, strength-based model, UDL, response to intervention, multidisciplinary team approach) [11,25,26] For example, collaboration could focus more on building school personnel and families' abilities to participate in early identification of children presenting developmental red flags or using coaching strategies with school personnel in the classroom or in the gymnasium.…”
Section: Discussionmentioning
confidence: 99%
“…An agreement was reached in the previous round Liaise with school-based occupational therapist to plan skill training Modified as "Liaise with other service providers (e.g., occupational therapists, speech therapist) and other school team members (e.g., special education teachers, learning support team) to plan skill training" Developing a transition plan with families (e.g., transition from primary school to secondary school) for students with motor impairments Modified as "Developing a transition plan with the family, student and school personnel (e.g., transition from primary school to secondary school) for students with motor impairments" Collaborating with orthotists, outpatient PTs/OTs and AT specialists to meet the needs of students 91% ✓ Collaborating with or coaching school personnel (e.g., educators, learning support team) to address the needs of students regarding14) setting educationally relevant goals and collaboratively plan on how to promote students` learning and achievement 15) balance, coordination, and strength 16) accommodations and individualized strategies for a child with a disability 17) adaptive equipment and its use for a student to maximize functions of students18) adapting activities in a gym or classroom to foster the participation of a child with a disability19) mobility of the students in the schools (e.g., classroom, bathroom, playground) 20) postural support and positioning of students during school activities (e.g., positioning of a student with dysphagia at lunch or sitting ergonomics) 21) creating a maximal stimulating environment for students with motor impairment 22) physical activity program for students23) learning new methods or ways to support a student in need24) safe manual handling of a students at school (e.g., in and out of a chair, stander or walker)25) equipment acquisition, modification, trails, adjustment and repair 26) fall prevention strategies 27) compensation strategies for students with motor impairment 28) orthotic support management 29) accommodations and individualized strategies for a student returning to school after an injury or surgery (return-to-school protocol) Facilitating inclusion of students with disabilities in PE class and other activities in the school 96% ✓ Collaborating with or coaching families to address the needs of children regarding: 32) setting educationally relevant goals and collaboratively plan on how to promote students` learning and achievement 33) accommodations and individualized strategies for a student with a disability 34) orthotic support and an exercise program for students who need orthotic support such as cerebral palsy, pes planus, etc. 35) a maximal stimulating environment for students with motor impairment 36) compensation strategies for a student with motor impairment 37) understanding what can be done at home to help the student function better in school 38) learning new methods or ways to support the student in need 39) physical activity programs for students 40) assistive devices for students with motor impairment 41) accommodations and individualized strategies for a child returning to school after an injury/surgery Strengthening the child's agency-as being agents to overcome environmental barriers at school 91% ✓ 46) Implementing appropriate activities of daily living (ADL) strategies into school routine to facilitate student access and participation of student with special needs in student activities 91% ✓ 47) Supporting equipment acquisition, modification, adjustment and repair to enhance the functioning of a student in in school, home and community 87% ✓ 48) Getting in...…”
mentioning
confidence: 99%
“…The first thing that can actually make a difference is the type and severity of disability. Numerous studies on the subject have shown significant differences in the time and manner in which it carries out the process of adaptation to the disability of a child [5]. Specifically in relation to the type and severity of disability that is diagnosed, the parents expect a certain kind of development and the type of complications related to it.…”
mentioning
confidence: 99%